In situ quantitative three-dimensional characterisation of sub-indentation cracking in polycrystalline alumina - Vertyagina, Y; Mostafavi, M; Reinhard, C; Atwood, R; Marrow, T (Elsevier, 2014)
The three-dimensional deformation beneath a Vickers indentation in polycrystalline alumina has been measured, in situ, by digital volume correlation of high resolution synchrotron X-ray computed tomographs. The displacement fields at the peak indentation load and after unloading are used to study the shape and orientation of sub-surface cracks induced by the indentation; lateral cracking due to residual stresses, bounded by a system of radial cracks, is revealed. For the first time, it is shown that radial cracks have mixed mode opening displacements, which are affected by the relaxation of residual stresses via lateral cracking. This novel technique may find applications in the study of surface damage by abrasive wear in brittle materials. © 2014 Elsevier Ltd.